Time of Flight Size Control of Carbon Nanoparticles Using Ar+CH4 Multi-Hollow Discharge Plasma Chemical Vapor Deposition Method - Sung Hwa Hwang (Processes, 2021)
As the application of nanotechnology increases continuously, the need for controlled size nanoparticles also increases. Therefore, in this work, we discussed the growth mechanism of carbon nanoparticles generated in Ar+CH4 multi-hollow discharge plasmas. Using the plasmas, we succeeded in continuous generation of hydrogenated amorphous carbon nanoparticles with controlled size (25–220 nm) by the gas flow. Among the nanoparticle growth processes in plasmas, we confirmed the deposition of carbon-related radicals was the dominant process for the method. The size of nanoparticles was proportional to the gas residence time in holes of the discharge electrode. The radical deposition developed the nucleated nanoparticles during their transport in discharges, and the time of flight in discharges controlled the size of nanoparticles.